(untitled) (Journal of actual problems of jurisprudence, 2019)
In this paper, a comprehensive legal analysis of public access to information in the field of environmental protection and the use of natural resources in the Republic of Kazakhstan is carried out, the legal framework for ensuring, implementing and protecting the public’s right to access environmental information is considered. The subject of research is information that relates to the ecological state of the natural environment itself, as well as the human environment. The legal regulation of ensuring public access to environmental information on the norms of international law and the legislation of international law and the Republic of Kazakhstan has been studied. The need for public access to environmental information and its possession are essential for the effective and integrated solution of such tasks as ensuring the rational use of natural resources and protecting the environment. Only having reliable and complete, timely environmental information can be given an objective assessment, which may arise and / or already occurring environmental hazard, or the harmful effects of natural, man-made, anthropogenic factors on human health and the environment, and take steps to eliminate them . Particular attention is paid to the problems of the direct implementation of the provision of environmental information, as well as the role of the public in decision-making participation in the Republic of Kazakhstan. Key words: Ecology, the right to a favorable environment, environmental information, human and civil rights, access to information, natural resources.